2004
DOI: 10.4028/www.scientific.net/ddf.230-232.93
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Strain Relaxation in III-V Semiconductor Heterostructures

Abstract: Partially relaxed III–V heterostructures: GaAs/InGaAs and InP/InAlAs/InGaAs, with a small lattice mismatch, grown using molecular beam epitaxy under compressive or tensile misfit stress at the (001) interface, have been investigated by means of high-resolution X-ray diffractometry, atomic force microscopy and generalized ellipsometry. Additionally, transmission electron microscopy and electron-beam induced current in a scanning electron microscope have been employed to reveal misfit dislocations at the heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…dislocation nucleation and glide. As a consequence, the asymmetric 2D network of  and  dislocations, running in two perpendicular 110 directions is usually formed, resulting in anisotropic misfit strain relaxation of the epitaxial layer in these directions [11][12][13][14][15][16][17]. Indeed, our previous studies on the GaInNAs/GaAs heterostructure showed a distinct anisotropy of strain relaxation related to the asymmetry in formation of interfacial dislocation network [8].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…dislocation nucleation and glide. As a consequence, the asymmetric 2D network of  and  dislocations, running in two perpendicular 110 directions is usually formed, resulting in anisotropic misfit strain relaxation of the epitaxial layer in these directions [11][12][13][14][15][16][17]. Indeed, our previous studies on the GaInNAs/GaAs heterostructure showed a distinct anisotropy of strain relaxation related to the asymmetry in formation of interfacial dislocation network [8].…”
Section: Resultsmentioning
confidence: 98%
“…The cross-hatch surface morphology is usually recognized to be directly related with strain relaxation via threading dislocation glide which results in both surface step and misfit dislocation formation [9,10]. Such a morphology is often observed during strain relaxation in many III-V lattice mismatched semiconductor systems, such as GaInAs/GaAs [11,12] or GaNAs/GaAs [13,14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these devices are based on thin films and grown epitaxially on limited lattice-matched substrates such as Al 2 O 3 , Si (111), GaN bulk, etc. However, even a slight lattice mismatch between the substrate and the grown films induces significant strain [15][16][17][18], which is generally relaxed through physical defect formation (threading dislocations, basal plane stacking faults, slip planes, etc [19][20][21][22]), but these defects significantly affect device performance [23][24][25][26][27]. Au is used for making electrode patterns on III-nitride-based devices because of its exceptional electrical properties; however, it makes a Schottky contact with GaN thin films, which is extremely important for some devices like diodes, photodetector, switches, etc, for the effective transport/separation of charge carriers.…”
Section: Introductionmentioning
confidence: 99%